2020
DOI: 10.3390/w12113082
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Hydrological Evaluations of Multiple Satellite Precipitation Products in the Yellow River Source Region of China

Abstract: Comprehensively evaluating satellite precipitation products (SPPs) for hydrological simulations on watershed scales is necessary given that the quality of different SPPs varies remarkably in different regions. The Yellow River source region (YRSR) of China was chosen as the study area. Four SPPs were statistically evaluated, namely, the Tropical Rainfall Measurement Mission (TRMM) Multisatellite Precipitation Analysis (TMPA) 3B42V7, Precipitation Estimation from Remotely Sensed Information using Artificial Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…The results indicated that GSMaP-Gauge V7 fits well with the observed runoff in monthly simulations and presents better ability to reproduce runoff changes than 3B42V7 does. Most of previous studies demonstrated that GSMaP-Gauge presents a better hydrological ability than GSMaP-MVK at daily and sub-daily time scales whether in the rain-gauge-based benchmarked parameter scheme or the input-specific recalibration scheme [63,66]. Similarly, this study found that GSMaP-Gauge demonstrates prominently better performance in capturing daytime precipitation dynamics in YRSR than GSMaP-MVK does.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The results indicated that GSMaP-Gauge V7 fits well with the observed runoff in monthly simulations and presents better ability to reproduce runoff changes than 3B42V7 does. Most of previous studies demonstrated that GSMaP-Gauge presents a better hydrological ability than GSMaP-MVK at daily and sub-daily time scales whether in the rain-gauge-based benchmarked parameter scheme or the input-specific recalibration scheme [63,66]. Similarly, this study found that GSMaP-Gauge demonstrates prominently better performance in capturing daytime precipitation dynamics in YRSR than GSMaP-MVK does.…”
Section: Discussionsupporting
confidence: 59%
“…Post-real-time SPPs generally show better performance than their near-time-time versions because of the gauge-based adjustment in several regions of the world [16,[60][61][62][63]. However, the post-real-time product GSMaP-MVK significantly overestimates precipitation with higher overestimation magnitudes than the near-real-time product GSMaP-NRT-Gauge (Figures 3 and 6), and GSMaP-MVK presents the lower overall score than GSMaP-NRT-Gauge (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…The literature review revealed that the performance evaluation of SRPs is essential before their direct application in any region [7,[14][15][16]. In this regard, several researchers have evaluated the accuracy of different SRPs in several countries-for instance, in America [17], Brazil [18], China [19][20][21], Italy [22], Iran [23], Malaysia [24], Pakistan [14], Taiwan [25], and Saudi Arabia [26]. Huang et al [25] assessed the error characteristics of PERSIANN family products in the whole of Taiwan and concluded that all products underestimated the rainfall amount over most parts of the country.…”
Section: Introductionmentioning
confidence: 99%
“…The Center for Hydrometeorology and Remote Sensing (CHRS) [11] at the University of California, Irvine (UCI), developed the [12][13][14] (Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks) PERSIANN system, which uses neural network function classification/approximation procedures to calculate an estimate of rainfall rate at each 0.25 • × 0.25 • pixel of an infrared brightness temperature image provided by geostationary satellites. PERSIANN-CDR [15][16][17] offers daily worldwide rainfall information at a 0.25 • grid scale. PERSIANN-CCS [18][19][20] is a cloud segmentation technique with customizable thresholds.…”
Section: Introductionmentioning
confidence: 99%